O mercado imobiliário e a reinvenção da Ribeira, Natal - RN: verticalizar para renovar? - Nascimento, Ingrid Graziele Reis do (2012)
The real estate dynamic originates new spatial forms, which can determine new uses and new places. We tried to analyze this work, the spatial transformations in the Ribeira district, Natal / RN, due to the advancement of the housing market that is gradually transforming the landscape with the introduction of new types of housing, especially by verticalization. The verticalization of the neighborhood occurs almost at once, changing the local landscape. Notwithstanding this process, given the rapid growth of Natal in the last two decades and the strategic location of the neighborhood, it is pertinent to note that, if not the process of vertical integration, perhaps the neighborhood had been at the mercy of other urban interventions and other approach the real estate market. The research used as instruments interviews with actors who work in the property market in the town and representatives of organizations that have implemented major legislation in the area, the Instituto de Patrimônio Histórico e Artístico Nacional (IPHAN) and the Secretaria de Meio Ambiente e Urbanismo (SEMURB) as well as photographs on the area, in order to verify this new configuration that has been consolidated in the district. To support the theoretical discussion, there was a documentary and bibliographical research. In this way, the object of study of this search sees the uniqueness of urban renewal in the district of Ribeira and its relationship with the historic preservation laws and incentives for residential occupation in the neighborhood, especially regarding the vertical building